Citrate Anticoagulation for Continuous Renal Replacement Therapy in Critically Ill Patients: Success and Limits - Filippo Mariano; Daniela Bergamo; Ezio Nicola Gangemi; Zsuzsanna Hollo'; Maurizio Stella; Giorgio Triolo (International Journal of Nephrology)
Citrate anticoagulation has risen in interest so it is now a real alternative to heparin in the ICUs practice. Citrate provides a regional anticoagulation virtually restricted to extracorporeal circuit, where it acts by chelating ionized calcium. This issue is particularly true in patients ongoing CRRT, when the “continuous” systemic anticoagulation treatment is per se a relevant risk of bleeding. When compared with heparin most of studies with citrate reported a longer circuit survival, a lower rate of bleeding complications, and transfused packed red cell requirements. As anticoagulant for CRRT, the infusion of citrate is prolonged and it could potentially have some adverse effects. When citrate is metabolized to bicarbonate, metabolic alkalosis may occur, or for impaired metabolism citrate accumulation leads to acidosis. However, large studies with dedicated machines have indeed demonstrated that citrate anticoagulation is well tolerated, safe, and an easy to handle even in septic shock critically ill patients.